Environmentally friendly extraction of gold from refractory concentrate using a copper – ethylenediamine – thiosulfate solution. (20th March 2019) - Wang, Qiang; Hu, Xianzhi; Zi, Futing; Yang, Peng; Chen, Yunlong; Chen, Shuliang
Abstract: The growing environmental concerns associated with the use of cyanides and their toxicity have led to the prohibition of cyanidation-based gold leaching in many countries, necessitating the search for other extraction methods. Herein, we show that thiosulfate leaching presents an alternative green way of gold extraction from S- and As-rich refractory gold concentrates, revealing the importance of oxidative ore pretreatment. Prior to leaching, samples were oxidized by roasting, with the optimum roasting temperature (642 °C) and time (240 min) determined using the response surface method. Subsequently, the roasted residues were subjected to cyanidation, copper – ammonia – thiosulfate system, and copper – ethylenediamine – thiosulfate system treatment. As a result, 18-h cyanidation achieved a gold extraction efficiency of 80.6%, with the consumption of NaCN equaling 1.05 kg/t, whereas the corresponding values for 1.5 h copper – ammonia – thiosulfate treatment equaled 63.0% and 11.3 kg/t. Importantly, 4 h copper – ethylenediamine – thiosulfate system treatment (5 mM copper ion, 10 mM ethylenediamine, 0.1 M thiosulfate, pH = 8–11, liquid-to-solid ratio = 3, stirring speed = 250 rpm) achieved a gold extraction efficiency of 80.3%, with the corresponding thiosulfate consumption equaling only 4.14 kg/t. Thus, copper – ethylenediamine – thiosulfate leaching proved to be an efficient, environmentally friendly, and low-cost method, being well-suited for gold extraction from roasted residues. Highlights: Copper – ethylenediamine – thiosulfate leaching is described as an alternative green way of gold extraction. Under optimal conditions, a gold extraction efficiency of 80.3% is achieved. The developed low-cost and environmentally friendly method is almost as effective as cyanidation.